Bridging taxonomic and disciplinary divides in infectious disease - Borer, Elizabeth T.; Antonovics, Janis; Kinkel, Linda L.; Hudson, Peter J.; Daszak, Peter; Ferrari, Matthew J.; Garrett, Karen A.; Parrish, Colin R.; Read, Andrew F.; Rizzo, David M. (My University, 2011)
Pathogens traverse disciplinary and taxonomic boundaries, yet infectious disease research occurs in many separate disciplines including plant pathology, veterinary and human medicine, and ecological and evolutionary sciences. These disciplines have different traditions, goals, and terminology, creating gaps in communication. Bridging these disciplinary and taxonomic gaps promises novel insights and important synergistic advances in control of infectious disease. An approach integrated across the plant-animal divide would advance our understanding of disease by quantifying critical processes including transmission, community interactions, pathogen evolution, and complexity at multiple spatial and temporal scales. These advances require more substantial investment in basic disease research.
Citation: Borer, E.T., & Antonovics, J. (2011). Bridging Taxonomic and Disciplinary Divides in Infectious Disease. EcoHealth 8, 261–267. https://doi.org/10.1007/s10393-011-0718-6
Keywords: Epidemics; Within-host dynamics; Prediction; Prevention; Cross-species transmission; Invasive species